2023
DOI: 10.3389/fgene.2023.1135404
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and immune cells in medulloblastoma

Abstract: Medulloblastoma (MB) is a highly malignant childhood tumor of the cerebellum. Transcriptional and epigenetic signatures have classified MB into four molecular subgroups, further stratified into biologically different subtypes with distinct somatic copy-number aberrations, driver genes, epigenetic alterations, activated pathways, and clinical outcomes. The brain tumor microenvironment (BTME) is of importance to regulate a complex network of cells, including immune cells, involved in cancer progression in brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 179 publications
0
5
0
Order By: Relevance
“…4D, and listed in Additional file 9). Thus, the use of this nutraceutical in a pill formula for systemic Ferrucci et al Journal of Translational Medicine (2024) 22:574 applications could be further envisioned as immunomodulant agent for the adjuvant therapy (during or after chemotherapeutics) with the aim to restore the innate immune response in those solid tumors characterized by immunosuppression driven by PI3K-Akt and TGF-β pathways dysregulation (e.g., brain tumors, medulloblastoma [117,118] and triple negative breast cancer [119]), once tested its pharmacokinetics and tissue biodistribution in vivo. Future studies will address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…4D, and listed in Additional file 9). Thus, the use of this nutraceutical in a pill formula for systemic Ferrucci et al Journal of Translational Medicine (2024) 22:574 applications could be further envisioned as immunomodulant agent for the adjuvant therapy (during or after chemotherapeutics) with the aim to restore the innate immune response in those solid tumors characterized by immunosuppression driven by PI3K-Akt and TGF-β pathways dysregulation (e.g., brain tumors, medulloblastoma [117,118] and triple negative breast cancer [119]), once tested its pharmacokinetics and tissue biodistribution in vivo. Future studies will address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the biomarkers with significant survival outcomes correlated with previously reported oncogenes. For example, the CBFA complex, which includes CBFA2T3 ( Hendrikse et al, 2022 ; Gorini et al, 2023 ), is suggested to play a critical role in tumor development through its interactions with epigenetic modifiers, contributing to the pathogenesis of medulloblastoma . Similarly, the study by Menyhárt et al (2019) demonstrated epigenetic changes in the RPTOR gene, along with other identified biomarkers, in classifying non-WNT/non-SHH medulloblastomas .…”
Section: Discussionmentioning
confidence: 99%
“…The most common form of this is within the context of CpG islands, which are frequently found near the promoter region of genes. Methylation of these islands results in CpG island hypomethylation has also been revealed in medulloblastoma [7]. In the SHH subgroup, VAV1 is an oncogene that is hypomethylated, leading to an increase in expression and therefore tumorigenic potential [17].…”
Section: Introductionmentioning
confidence: 93%